2015
DOI: 10.1007/s00787-015-0701-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific and time-dependent effects of prenatal stress on the early behavioral symptoms of ADHD: a longitudinal study in China

Abstract: There is increasing evidence that prenatal stressful life events (SLEs) may be a potential risk factor for attention-deficit hyperactivity disorder (ADHD), but the sex-specific and time-dependent effects of prenatal stress on ADHD are less clear. In this prospective longitudinal study, data on prenatal SLEs during different stages of gestation and indicators of buffers against stress, including maternal social support and avoidance coping, were obtained from 1765 pregnant women at 32 weeks of gestation. The be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 30 publications
5
64
0
Order By: Relevance
“…These findings are similar to Zhu et al (2015), who found that, for mothers experiencing stressful life events in pregnancy, avoidant coping predicted higher odds of maternal-rated ADHD symptoms in children. These findings also are similar to Oni and colleagues (Oni et al, 2015;Oni et al, 2012) who found that humour reduced the odds of both gestation diabetes and maternal posttraumatic stress in mothers exposed to a natural disaster, while denial and venting increased the odds.…”
Section: Coping and Child Developmentsupporting
confidence: 80%
See 3 more Smart Citations
“…These findings are similar to Zhu et al (2015), who found that, for mothers experiencing stressful life events in pregnancy, avoidant coping predicted higher odds of maternal-rated ADHD symptoms in children. These findings also are similar to Oni and colleagues (Oni et al, 2015;Oni et al, 2012) who found that humour reduced the odds of both gestation diabetes and maternal posttraumatic stress in mothers exposed to a natural disaster, while denial and venting increased the odds.…”
Section: Coping and Child Developmentsupporting
confidence: 80%
“…There is some evidence that, in response to Hurricane Katrina, maternal coping strategies reduced the negative impact of this stressor on mothers' subsequent mental health (Oni, Harville, Xiong, & Buekens, 2012), and were also related to reduced pregnancy complications (Oni, Harville, Xiong, & Buekens, 2015). In the only study that could be found regarding maternal coping, prenatal stress and child development, Zhu et al (2015) found that higher maternal avoidant coping increased the risk of maternalrated Attention-deficit Hyperactivity Disorder (ADHD) symptoms in children following prenatal exposure to stressful life events. Maternal coping may mitigate the negative effects of prenatal maternal stress on child development, but investigations of coping in the prenatal stress literature are only in the preliminary stages.…”
Section: Explaining and Reducing The Negative Effects Of Prenatal Matmentioning
confidence: 85%
See 2 more Smart Citations
“…Boys were also more vulnerable to ADHD symptoms in another prospective, longitudinal study. They were twice as likely to have clinically-relevant ADHD symptoms, if their mothers suffered life events that they evaluated as extremely stressful during their second pregnancy trimester [28]. For girls, severe stressful events were only predictive of ADHD if they ensued during the third trimester of pregnancy.…”
Section: Attention Deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%